Therapeutic Potential of Exosomes Derived from Diabetic Adipose Stem Cells in Cutaneous Wound Healing of db/db Mice - Hsiang-Hao Hsu; Aline Yen Ling Wang; Charles Yuen Yung Loh; Ashwin Alke Pai; Huang-Kai Kao (MDPI AG, 2022)
(1) Background: Diabetes impairs angiogenesis and wound healing. Paracrine secretion from adipose stem cells (ASCs) contains membrane-bound nano-vesicles called exosomes (ASC-Exo) but the functional role and therapeutic potential of diabetic ASC-Exo in wound healing are unknown. This study aims to investigate the in vivo mechanistic basis by which diabetic ASC-Exo enhance cutaneous wound healing in a diabetic mouse model. (2) Methods: Topically applied exosomes could efficiently target and preferentially accumulate in wound tissue, and the cellular origin, ASC or dermal fibroblast (DFb), has no influence on the biodistribution pattern of exosomes. In vivo, full-thickness wounds in diabetic mice were treated either with ASC-Exo, DFb-Exo, or phosphate-buffered saline (PBS) topically. ASC-Exo stimulated wound healing by dermal cell proliferation, keratinocyte proliferation, and angiogenesis compared with DFb-Exo and PBS-treated wounds. (3) Results: Diabetic ASC-Exo stimulated resident monocytes/macrophages to secrete more TGF-β1 and activate the TGF-β/Smad3 signaling pathway. Fibroblasts activated by TGF-β1containing exosomes from ASCs initiate the production of TGF-β1 protein in an autocrine fashion, which leads to more proliferation and activation of fibroblasts. TGF-β1 is centrally involved in diabetic ASC-Exo mediated cellular crosstalk as an important early response to initiating wound regeneration. (4) Conclusions: The application of diabetic ASC-Exo informs the potential utility of a cell-free therapy in diabetic wound healing.